Analisis Distribusi Data Kualitas Jaringan 5G Menggunakan Kurva Normal T-Student: Studi Kasus di Indonesia - Angelina Estevani; Cindy Margaratha; Magdalene Isma; Jadiaman Parhusip (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
5G internet speed is an important indicator in assessing the quality of modern communications networks. This research aims to analyze the distribution of 5G internet speed data in Indonesia using the normal T-Student curve, especially in cases with a small sample size. Data was obtained from average 5G internet speed reports published by telecommunications service providers and network mapping platforms. The analysis results show that the T-Student normal curve is able to provide an accurate representation of 5G speed data in several areas with limited sample sizes. This research provides new insights into approaches to data analysis of telecommunications network quality, especially in Indonesia.